45.2k views
1 vote
5x-4y-6z = -3
X-3y+z=-1
-3x-6y+7z=1

2 Answers

2 votes

Final answer:

To solve the given system of equations, we can use the method of elimination. The solution is x = 2, y = -1, and z = 1.

Step-by-step explanation:

To solve the given system of equations:

5x-4y-6z = -3
X-3y+z=-1
-3x-6y+7z=1

We can use the method of substitution or elimination to solve for the values of x, y, and z.

Let's use the method of elimination:

  1. Multiply the second equation by 5 and the third equation by 3 in order to make the coefficients of x in the second and third equations equal to that of the first equation.
  2. Add the resulting equations together to eliminate x:
  3. Solve the resulting system to find the values of y and z.
  4. Substitute the values of y and z back into any of the original equations to solve for x.

The solution is x = 2, y = -1, and z = 1.

User Expenguin
by
5.6k points
4 votes

Answer:


x=-(41)/(55),y=(2)/(55),z=-(8)/(55)

Step-by-step explanation:


5x-4y-6z=-3...............eq(1)\\\\x-3y+z=-1.....................eq(2)\\\\-3x-6y+7z=1.................eq(3)


eq(1)-5* eq(2)


5x-4y-6z-5(x-3y+z)=-3-5* (-1)\\\\11y-11z=2\\\\y-z=(2)/(11)...................eq(4)


3* eq(2)+eq(3)


3(x-3y+z)-3x-6y+7z=3* (-1)+1\\\\-15y+10z=-2\\\\-y+(2)/(3)z=-(2)/(15).........eq(5)


eq(4)+eq(5)


y-z-y+(2)/(3)z=(2)/(11)-(2)/(15)\\\\-(1)/(3)z=(8)/(165)\\\\z=-(8* 3)/(165)\\\\z=-(8)/(55)

From
eq(4)


y=z+(2)/(11)=-(8)/(55)+(2)/(11)\\\\y=(2)/(55)

Substitute the value of
y and
z in
eq(2)


x-3* (2)/(55)-(8)/(55)=-1\\\\x-(14)/(55)=-1\\\\x=-1+(14)/(55)\\\\x=(41)/(55)

User Feoh
by
5.1k points